Rescue of Functional CFTR Channels in Cystic Fibrosis: A Dramatic Multivalent Effect Using Iminosugar Cluster‐Based Correctors. Issue 15 (13th September 2013) - Compain, Philippe; Decroocq, Camille; Joosten, Antoine; de Sousa, Julien; Rodríguez‐Lucena, David; Butters, Terry D.; Bertrand, Johanna; Clément, Romain; Boinot, Clément; Becq, Frédéric; Norez, Caroline
Abstract Cystic fibrosis is caused by a mutation in the gene for the cystic fibrosis transmembrane conductance regulator (CFTR) protein. N‐butyl 1‐deoxynojirimycin (N‐Bu DNJ), a clinical candidate for the treatment of cystic fibrosis, is able to act as a CFTR corrector by overcoming the processing defect of the mutant protein. To explore the potential of multivalency on CFTR correction activity, a library of twelve DNJ click clusters with valencies ranging from 3 to 14 were synthesized. Significantly, the trivalent analogues were found to be up to 225‐fold more potent than N‐Bu DNJ and up to 1000‐fold more potent than the corresponding monovalent models. These results provide the first description of a multivalent effect for correcting protein folding defects in cells and should have application for the treatment of a number of protein folding disorders. Preliminary mechanistic studies indicated that CFTR correction activity enhancement was not due to a multivalent effect in ER‐glucosidase inhibition or to a different mode of action of the multivalent iminosugars.